Changes of Gene Expression in the Developing Brain by Acute Ethanol Exposure - Kim, Nayoung; Soo Kang, Sang; Sung Choi, Wan (Current Psychopharmacology, 2012)
Ethanol is one of the most common teratogens, causing a broad range of physiological, neuronal and behavioral problems, named as fetal alcohol spectrum disorder (FASD). Expression of various molecules involved in apoptosis, signaling pathways, and innate immune system, has been shown to change upon acute ethanol exposure. Gene expression profiling has been attempted by several groups, but comprehensive understanding is required, considering different experimental protocols used by each group. In this review, we summarize previously published reports of transcriptome analyses and our own previously unpublished results of cDNA microarray, according to developmental stages of brain and discuss about what we have learned from the results.
Keywords: PI3K signaling pathways